Taguchi-Based Optimization of Mix Design and Mechanical Properties of Epoxy Polymer Concrete with Recycled Coarse Aggregate - Khusnul Aldi Saputra; Eva Arifi; Desy Setyowulan (The Indonesian Institute of Science and Technology Research, 2026)
This study examines the mix design and mechanical properties of epoxy polymer concrete utilizing fully recycled coarse aggregate and fly ash as a mineral filler through a Taguchi-based optimization framework. An L9 orthogonal array including four control factors and three levels was employed to incorporate epoxy resin content, resin–hardener ratio, coarse-to-fine aggregate ratio, and class C fly ash proportion. All mixtures were designed using the absolute-volume method so that the total volume of the constituent materials exactly matched the target specimen volume. The research test object was a 50 × 50 × 50 mm cube that follows the experimental design in method B of the ASTM C 579-96 standard for polymer concrete. Cube specimens tested at seven days for compressive strength and static modulus of elasticity based on the stress–strain response. The compressive strengths varied from around 11.14 to 57.20 MPa, whereas the average static modulus ranged from about 0.58 GPa to nearly 2.95 GPa. Taguchi analysis and ANOVAs conducted on both mean strength and S/N ratios consistently revealed epoxy content, resin–hardener ratio, and coarse-to-fine aggregate ratio as the dominant factors, while fly ash served as a secondary modifier. The optimal combination comprises 25% polymer matrix of the total specimen volume, a resin–hardener ratio of 1.5:1, a balanced coarse-to-fine aggregate ratio of 1:1, and an quantity of fly ash around 30% of the total volume of fine aggregate. According to Taguchi analysis, this optimal combination leads to a predicted compressive strength of approximately 52.89 to 61.23 MPa. An independent confirmation mixture prepared at this optimal combination achieved an average strength of about 57.46 MPa, aligning well with Taguchi predictions. The linear relationship between compressive strength and static modulus of elasticity shows a positive correlation. This linear relationship enables a straightforward empirical formula to determine the stiffness of epoxy polymer concrete with recycled coarse material, predicated on its compressive strength.